Impact of Covid–19 on MSME Sector in India: A Literature Review - Saritha, Mora (International Journal of Economics and Financial Issues, 2022)
The world over has witnessed the pandemic called Covid-19 over the last 2 years. The unknown before and unanticipated doom has created havoc in an unprecedented manner. The adverse impact of this pandemic is globally recognized and it spread as a contagion affecting trade across nations undesirably. India being second largest populous country is no exception to this adversity. The lock down which is considered as one of the means to contain the spread of this pandemic was implemented in our country since March 2020, however unlock situation is being introduced in a phased manner. Though lock down was effective in containing the spread of pandemic, it was enabling the economy to cripple from progressing. Industries in manufacturing and services sector could not able to sustain lockdown and were pushed to doldrums. Majority of the enterprises suffered huge losses and were on the verge of closure. The MSME (Micro, Small and Medium enterprise) sector has been seriously hit due to this lock down measure. The present article reflects the review of literature surrounding MSMEs spanning from the last 2 years. The literature has been collected from various journal articles, government reports, newspaper articles etc.